2021
DOI: 10.1186/s13578-021-00733-y
|View full text |Cite
|
Sign up to set email alerts
|

The eukaryotic initiation factor 5A (eIF5A1), the molecule, mechanisms and recent insights into the pathophysiological roles

Abstract: Since the demonstration of its involvement in cell proliferation, the eukaryotic initiation factor 5A (eIF5A) has been studied principally in relation to the development and progression of cancers in which the isoform A2 is mainly expressed. However, an increasing number of studies report that the isoform A1, which is ubiquitously expressed in normal cells, exhibits novel molecular features that reveal its new relationships between cellular functions and organ homeostasis. At a first glance, eIF5A can be regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 165 publications
0
21
0
Order By: Relevance
“…Translation is a critical component in the regulation of multiple developmental pathways, cell activation, and cancer progression (Fabbri et al, 2021; Sanchez et al, 2016; Sonenberg and Hinnebusch, 2007; Tahmasebi et al, 2018). Within the broad realm of protein synthesis, hypusinated eIF5A while stimulating general translation, also drives specific translational programs impacting cancer, diabetes, and infectious diseases (Dever et al, 2014; Hoque et al, 2017; Kaiser, 2012; Tauc et al, 2021). Notably though the impact of eIF5A in erythropoiesis, a process that is particularly sensitive to translational regulation, has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translation is a critical component in the regulation of multiple developmental pathways, cell activation, and cancer progression (Fabbri et al, 2021; Sanchez et al, 2016; Sonenberg and Hinnebusch, 2007; Tahmasebi et al, 2018). Within the broad realm of protein synthesis, hypusinated eIF5A while stimulating general translation, also drives specific translational programs impacting cancer, diabetes, and infectious diseases (Dever et al, 2014; Hoque et al, 2017; Kaiser, 2012; Tauc et al, 2021). Notably though the impact of eIF5A in erythropoiesis, a process that is particularly sensitive to translational regulation, has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it is the only protein in eukaryotes and archaea to contain the amino acid hypusine [ N ε -(4-amino-2-hydroxybutyl)lysine], a modification that is essential for its activity (Park and Wolff, 2018; Saini et al, 2009; Wolff et al, 2007). eIF5A is required for the growth of S. cerevisiae (Chattopadhyay et al, 2008) and has also been shown to be highly expressed at all mouse embryonic stages, with hypusination required for muscle differentiation (Parreiras-e-Silva et al, 2010; Tauc et al, 2021). Moreover, in humans, heterozygous variants in EIF5A have recently been shown to cause a syndrome characterized by developmental delay, microcephaly, and congenital malformations (Faundes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…eIF5A has been reported to be the only protein containing hypusine and the subunit is activated by post-translational synthesis of hypusine [ 48 ]. It has been proposed that hypusinated eIF5A is a RNA binding protein associated with exportins [ 49 ]. Interestingly hypusinated eIF5A, which impacts protein synthesis was shown to be mainly localized in the cytoplasm [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…By facilitating translation elongation on ribosome pause sites e.g. PPX, eIF5A supports protein and organelle biogenesis, autophagy and immune functions 43 —all of which are key cellular pathways often deregulated in HD 1,3 . eIF5A is also involved in the regulation of key enzymes mediating polyamine metabolism 44 .…”
Section: Mainmentioning
confidence: 99%